Three dimensional porous monoliths from multi-walled carbon nanotubes and polyacrylonitrile. (May 2016) - Vipin, Adavan Kiliyankil; Fugetsu, Bunshi; Sakata, Ichiro; Tanaka, Hideki; Sun, Ling; Tanaka, Shunitz; Terrones, Mauricio; Endo, Morinobu; Dresselhaus, Mildred
Abstract: Three-dimensional (3D), porous monoliths with high electrical and thermal conductivities were produced by using unmodified multi-walled carbon nanotubes (CNTs) and polyacrylonitrile (PAN) as the starting compounds through a template-free thermally induced phase separation approach. Multi-walled CNTs in the PAN/CNT monoliths were fully dispersed and as a result, interconnected CNT networks with high uniformity were established. The average value of the porosity, surface area, electrical conductivity, thermal conductivity and mechanical strength were found to be 90%, 210 m 2 /g, 2.7 S/cm, 0.148 W/(m.K) and 1.1 MPa, respectively, for a 3D porous PAN/CNT monolith sample with a 33 wt% CNT loading. This new class of the CNT-based monolith opens up new possibilities for various practical applications.